Invasive Pigweed (Amaranthus spinosus) as a Potential Source of Plant Secondary Metabolites to Mitigate Enteric Methane Emissions in Beef Cattle - Wilmer Cuervo; Mariana Larrauri; Camila Gomez-Lopez; Nicolas DiLorenzo (Grasses)
Global beef demand will rise by 40 million tons in 30 years, increasing methane (CH4) emissions. Pigweed (Amaranthus spinosus), an invasive weed abundant in southeastern U.S. pastures, may mitigate CH4. Yet, its potential as a feed additive remains unexplored. The aim of this study was to evaluate the influence of pigweed and its extracts on ruminal fermentation and CH4 production. For Exp 1, ruminal fluid from three American Aberdeen steers was incubated with 0, 2.5%, 5%, or 10% of diet dry matter (DM) of roots, stems, leaves, seeds, or the whole pigweed plant (WHO). In Exp 2, extracts from the leaves and WHO were incubated under the same conditions. For the first experiment, 2.5% of the roots, 5% of the leaves, and 10% of the WHO decreased acetate and butyrate concentrations (p < 0.01). In contrast, the WHO, leaves, and seeds at 2.5% of DM increased propionate concentration (p = 0.05). Increasing levels of WHO, leaves, and seeds quadratically reduced CH4 (p < 0.001). The addition of 2.5 and 5% of leaves and WHO reduced in vitro CH4 production per gr of organic matter fermented (p < 0.01). In Exp 2, based on their CH4 mitigation, the leaves and WHO were extracted, and their phenol (3.2 and 1.1 mg/g of DM, respectively) and flavonoid (19.7 and 1.9 mg/g of DM, respectively) contents were determined. Extracts from WHO (2.5%) decreased acetate and CH4 (p < 0.05), while 5% inclusion decreased gas production and increased ruminal pH (p < 0.03). Leaf extracts (2.5%) increased propionate and reduced acetate: propionate (p < 0.05). The leaves and WHO extracts did not affect IVOMD at either inclusion level (p > 0.4). Extracts at 5% from WHO were more effective than that from leaves in reducing CH4 (27% vs. 4%). The evidence suggests that the inclusion of 2.5 to 5% of WHO extracts shifts ruminal fermentation towards propionate-producing impairing methanogenesis, representing a sustainable strategy to mitigate CH4. This hypothesis must be further assessed under in vivo supplementation of the extracts to beef cattle.